Corporate Entrepreneurship and Beyond-Connectivity Growth in the Telco-to-TechCo Transformation: Early Evidence from an Indonesian Telecommunications Operator - Rivki Suardi (Journal of Accounting and Finance Management, 2026)
This study examines how corporate entrepreneurship supports the Telco-to-TechCo transformation by enabling new business-to-business (B2B) digital revenue beyond legacy connectivity in Indonesia, a large mobile-first market where incumbents face pressure to diversify as core revenue matures. Using a qualitative single-case study with document analysis and source tracing, it analyzes an anonymized internal strategic transformation document from a large post-merger Indonesian operator, triangulated against audited annual reports, official disclosures, traced industry sources, and peer-reviewed literature. The analysis applies four lenses: corporate entrepreneurship, dynamic capabilities, strategic entrepreneurship, and business ecosystem theory. The findings document early transformation evidence rather than a completed transformation: a source-anchored rationale, a redefined commercial logic, an expanding portfolio across cloud, IoT, cybersecurity, data, and artificial intelligence infrastructure, an ecosystem-orchestration posture, and a Sell-Manage-Deliver operating model presented as intended design. An emerging enterprise technology unit reports early revenue growth treated as a management-disclosed indicator requiring further validation. The principal contribution is to position the transformation as a corporate entrepreneurship process rather than a technology adoption program, using a source-accountable single-case design. The study is limited by its single-case scope and reliance on a non-audited document for several indicators.